Western Medicine in India as a Colonial Case in Amitav Ghosh’s The Calcutta Chromosome (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper focuses on the introduction of Western medicine in colonial India and its relationship with indigenous Indian medical practices against the background of Amitav Ghosh’s The Calcutta Chromosome. It tries to locate an alternative narrative of the subalterns who, instead of conceding subordination, actually manipulate the state of the art of contemporary malaria research in early 20th century and reincarnate themselves in a futuristic New York but never let the elites discover their true motive. Simultaneously, it throws light on instances of epistemic violence because of cultural encounters.